2018
DOI: 10.1007/s10967-018-6360-9
|View full text |Cite
|
Sign up to set email alerts
|

Radiocarbon and radiocesium in litter fall at Kawamata, ~ 45 km NW from the Fukushima Dai-ichi nuclear power plant (Japan)

Abstract: Radiocarbon and radiocesium were measured on litter fractions (LF) collected on November 19 th , 2011 at 40 km NW of the FDNPP. The 137 Cs concentration is much higher in the lower fraction LFb at 226,650 ± 170 Bq kg-1 than in the upper fraction LFa at 7290 ± 40 Bq kg-1. From leaf-air 14 C comparison, no excess 14 C due to the FDNPP accident is detected in LFa deposited in 2010-2011. A significant 14 C difference of 1.4% exists between pine needles and deciduous leaves in LFb, which may be due either to post-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…In November 2011, a leaf litter sample was collected in Kawamata in northeast Japan and divided into two distinct fractions. Despite their quite high content of radiocesium, neither of the fractions yielded an increased 14 C concentration which was in concordance with the atmospheric level [ 98 ]. The radiocarbon screening of the surrounding of the FDNPP reactor buildings, which was conducted in the summer of 2012, has brought some interesting results.…”
Section: Fdnpp Impact On Radiocarbon Environmental Levelsmentioning
confidence: 74%
“…In November 2011, a leaf litter sample was collected in Kawamata in northeast Japan and divided into two distinct fractions. Despite their quite high content of radiocesium, neither of the fractions yielded an increased 14 C concentration which was in concordance with the atmospheric level [ 98 ]. The radiocarbon screening of the surrounding of the FDNPP reactor buildings, which was conducted in the summer of 2012, has brought some interesting results.…”
Section: Fdnpp Impact On Radiocarbon Environmental Levelsmentioning
confidence: 74%
“…Although previous dosimetric studies demonstrated that currently the internal exposure of both the local population and the decontamination workers remains minimal, both internal and external exposures of these groups should be studied over longer temporal periods to help understand the longterm impacts of this accident on exposed population groups. More research is also required to understand the fate and dynamics of other longer-lived radionuclides in the Fukushima www.soil-journal.net/5/333/2019/ SOIL, 5, 333-350, 2019 region including radiocarbon (Paterne et al, 2018;Povinec et al, 2016;Xu et al, 2016), plutonium and uranium isotopes (Jaegler et al, 2018;Zheng et al, 2013;Steinhauser, 2014) as they may be persistent in the environment even though many were emitted only at the trace and ultra-trace levels.…”
Section: Perspectives For Future Researchmentioning
confidence: 99%
“…There are few publications in international journals regarding the potential or effectiveness of the latter strategy (e.g. Pareniuk et al, 2015). Among the few available studies, Kobayashi et al (2014) grew thirteen plant species from three families (Asteraceae, Fabaceae, and Poaceae) in shallow and deeply cultivated fields where the 0-8 cm and 0-15 cm soil layers were respectively ploughed.…”
Section: Soil/farmland Decontaminationmentioning
confidence: 99%
“…Although previous dosimetric studies demonstrated that currently the internal exposure of both the local population and the decontamination workers remains minimal, both internal and external exposures of these groups should be studied over longer temporal periods to help understand longterm impacts of this and potentially other nuclear accidents on exposed population groups. More research is also required to understand the fate and dynamics of other longer-lived radionuclides in the Fukushima region including radiocarbon (Paterne et al, 2018;Povinec et al, 2016;Xu et al, 2016), plutonium and uranium isotopes (Jaegler et al, 2018;Zheng et al, 2013;Steinhauser, 2014) as they may be persistent in the environment even though many were emitted only at the trace and ultra-trace levels.…”
Section: Perspectives For Future Researchmentioning
confidence: 99%